CROSSING WORLDS: PORTAL FANTASY IN NOVEL THE LION THE WITCH AND THE WARDROBE, KOREAN NOVEL SOLO LEVELING AND COMIC MANGA THAT TIME I GOT REINCARNATED AS A SLIME - Iskandar, Iskandar; Priyawan, Pepen; Suswanto, Deni (Saksama: Jurnal Sastra, 2024)
This article explores the representation of portal fantasy in three distinct works: The Lion, the Witch and the Wardrobe by C.S. Lewis, Solo Leveling Volume 1 by Chu-Gong, and That Time I Got Reincarnated as a Slime Volume 1 by Fuse. The research problem centers on how the portal fantasy formula is adapted and represented in different literary forms novels and manga. Drawing on theories from Farah Mendlesohn on fantasy genres, E.M. Forster on key elements of novels, and Will Eisner on comics, the study employs a comparative literature approach and qualitative methods, including close reading and textual analysis. The analysis focuses on key elements such as setting, plot, motif, and character to uncover how these works embody the portal fantasy genre. The findings reveal that each work utilizes the portal concept uniquely to achieve distinct narrative purposes: The Lion, the Witch and the Wardrobe emphasizes the contrast between the real world and a magical one, offering moral and exploratory adventures, Solo Leveling presents a dynamic, challenge-filled journey that serves as a metaphor for personal growth and transformation and That Time I Got Reincarnated as a Slime explores themes of identity and adaptation through the protagonist’s reincarnation in a fantastical world. The results highlight the versatility of the portal fantasy genre in conveying complex themes of transformation, identity, and exploration across different media. This study contributes to a deeper understanding of how portal fantasy functions within various literary forms, offering insights into its narrative potential and thematic richness.